Portrait of Ulayat Land Conflicts in Minangkabau Customary Law Community: Alternative Resolutions Under Islamic Law - Iswari, Fauzi; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego (Institut Agama Islam Negeri Curup, 2025)
This research aims to describe an overview of the existence of ulayat land in the Minangkabau customary law community, the characteristics of ulayat land conflicts that occur in the Minangkabau customary law community, and alternative solutions to conflict resolution of ulayat land in the Minangkabau customary law community according to Islamic law. This research is a normative legal research conducted using the comparative legal study approach method. The legal material used comes from library materials or secondary data, then the data is analysed qualitatively juridically. Based on the results of the research, it can be explained that the existence of ulayat land in customary law communities has been recognised in various laws and regulations. However, horizontal and vertical conflicts still occur in the community. Litigation settlement, it turns out, has not been able to bring justice to customary law communities. This is because the resolution of conflicts over ulayat rights tends to prioritise the aspect of formal legality alone. Therefore, in resolving various customary land conflicts that occur, it is a necessity for Minangkabau customary law communities that make Islam the only religion adopted to consider ways of dispute resolution based on Islamic law, such as through ishlah or peace. Thus, in the midst of legal pluralism that applies in Indonesia, in addition to State law, the provisions in Islamic law and customary law should also be used as a reference in resolving any ulayat land conflicts in the community.